2021
DOI: 10.1111/fima.12338
|View full text |Cite
|
Sign up to set email alerts
|

Working hard for long‐distance relationships: Geographic proximity and relationship‐specific investments

Abstract: Suppliers that are farther away from their customers make more relationship-specific investments (RSI). This association is more pronounced when it is less costly for the customer to switch to alternative suppliers and when the supplier operates in relatively opaque information environments. Using the introduction of new airline routes as an exogenous shock to the distance between supply chain partners, we show that the relation between supplier RSI and distance may be causal. We also provide evidence that sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Because geographical proximity is positively related to information acquisition costs (Giroud, 2013), it is difficult for customers to provide timely transactional information to suppliers or to monitor supplier behavior [14]. Kershen Huang et al (2021) analyze the switching costs of customers switching suppliers and confirm this inference [15]. They used the supplier's industry size, the supplier's market competitiveness, and the supplier's product similarity to measure the customer's replacement cost to the supplier and found that in a long-distance relationship, customers tend to have more similar suppliers to choose from and the goods of a single supplier are not highly unique.…”
Section: Geographic Distancementioning
confidence: 99%
“…Because geographical proximity is positively related to information acquisition costs (Giroud, 2013), it is difficult for customers to provide timely transactional information to suppliers or to monitor supplier behavior [14]. Kershen Huang et al (2021) analyze the switching costs of customers switching suppliers and confirm this inference [15]. They used the supplier's industry size, the supplier's market competitiveness, and the supplier's product similarity to measure the customer's replacement cost to the supplier and found that in a long-distance relationship, customers tend to have more similar suppliers to choose from and the goods of a single supplier are not highly unique.…”
Section: Geographic Distancementioning
confidence: 99%
“…Our results show that the variation in social capital across US counties has important implications on firms' investor base, which may be a potential mechanism behind the documented benefits of social capital. On a broader scale, this paper also relates to the extant literature on the empirical relations between geographic characteristics and financial markets (e.g., Francis et al, 2016;Huang et al, 2021;John et al, 2011;Malloy, 2005).…”
Section: Introductionmentioning
confidence: 99%